Sex ratio of newborn infants born to pregnant women with severe chronic constipation - Andrew E Czeizel; Erzsébet H Puhó; Ferenc Bánhidy (Clinical Epidemiology, 2010)
Andrew E Czeizel1, Erzsébet H Puhó1, Ferenc Bánhidy21Foundation for the Community Control of Hereditary Diseases, 2Second Department of Obstetrics and Gynecology, Semmelweis University, School of Medicine, Budapest, HungaryAbstract: There was a significant male excess in the newborns of pregnant women with severe chronic constipation during pregnancy compared to pregnant women without constipation and pregnant women with new onset severe constipation, during pregnancy.Keywords: constipation, pregnancy, birth outcomes, sex ratio, male excess